Middle cerebral artery infarction, A rare complication of intracranial cryptococcoma in an immunocompetent patient: A case report and literature review - Li, Ying-Ching; Tseng, Chun-Chia; Chien, Shuo-Chi; Huang, Sheng-Han; Chang, Tin-Wei; Chen, Chun-Ting; Tu, Po-Hsun; Liu, Zhuo-Hao; Huang, Yin-Cheng (Frontiers in Surgery, 2023)
Background This report presents the first case of intracranial cryptococcoma arising from the right frontal lobe causing right middle cerebral artery infarction. Intracranial cryptococcomas traditionally occur in the cerebral parenchyma, basal ganglia, cerebellum, pons, thalamus, and choroid plexus; they may mimic intracranial tumors, but seldom cause infarction. Of the 15 cases of pathology-confirmed intracranial cryptococcomas in the literature, no case has been complicated by middle cerebral artery (MCA) infarction. Here, we discuss a case of intracranial cryptococcoma with an ipsilateral middle cerebral artery infarction. Case Description A 40-year-old man was referred to our emergency room due to progressive headaches and acute left hemiplegia. The patient was a construction worker with no history of avian contact, recent travel, or human immunodeficiency virus (HIV) infection. Brain computed tomography (CT) showed an intra-axial mass, and subsequent magnetic resonance imaging (MRI) delineated a large mass of 53 mm in the right middle frontal lobe and a small lesion of 18 mm in the right caudate head, with marginal enhancement and central necrosis. A neurosurgeon was consulted in view of the intracranial lesion, and the patient underwent en-bloc excision of the solid mass. The pathology report later identified a Cryptococcus infection rather than malignancy. The patient underwent 4 weeks of postoperative treatment with amphotericin B plus flucytosine; he then received subsequent oral antifungal treatment for 6 months, and had neurologic sequelae that manifested as left side hemiplegia. Conclusion Diagnosis of fungal infections in the CNS remains challenging. This is especially true of Cryptococcus CNS infections that present as a space-occupying lesion in an immunocompetent patient. A Cryptococcus infection should be considered in the differential diagnoses in patients with brain mass lesions, as this infection can be misdiagnosed as a brain tumor.